Do first responders and populations perceive risks similarly? A comparative study of seven countries - Stolero, Nathan; Elkady, Sahar; Labaka, Leire; Siman Tov, Maya; Peleg, Kobi; Adini, Bruria (Frontiers in Psychology, 2024)
Introduction Risk perception illustrates the subjective evaluation of individuals concerning the characteristics, severity, and capacity to cope with potential hazards. Risk perception influences attitudes and actions individuals take to protect themselves from future threats. Risk perceptions might change among different stakeholder groups such as society and first responders. Identifying risk perceptions of stakeholders is essential to establish effective protective measures. Method This study investigated the commonalities and diversities in risk perception among first responders and the public, within and between seven European and beyond countries. A self-administered questionnaire was used to gather data from both first responders and civilians. They were asked to assess their risk perception level for five categories of risks (Extreme weather-related events, nature-related events, social disruptions, critical services dependencies, and pandemics). Results Using Univariate Analysis of Variance showed disparity concerning both the levels of risk perception between the public and first responders, as well as their relative ranking. For example, concerning extreme weather-related and nature-related events, risk perception levels of the first responders is higher than that of the population in six out of the seven studied countries. In contrast, the population’s risk perception is higher compared to the first responders in six out of the seven countries, concerning critical infrastructure dependencies and pandemics. Discussion The relative gaps between the first responders versus the population, within each country, vary considerably. Norway for example presents significant differences between the two internal populations concerning all risks (except for extreme weather), while in Sweden, no significant gaps were identified, concerning all five risks.